Hydrodynamics of mountain‐river confluences and its relationship to sediment transport. Issue 4 (18th April 2017) - Guillén Ludeña, S.; Cheng, Z.; Constantinescu, G.; Franca, M. J.
Abstract: Mountain confluences are characterized by narrow and steep tributaries that provide important sediment load to the confluence, whereas the main channel supplies the dominant flow discharge. This results in a marked bed discordance between the tributary and main channel which induces key differences in the hydromorphodynamics of the confluence when compared to concordant bed and some common types of discordant bed confluences. The processes of initiation and maintenance of the morphology of confluences are still unknown, and research linking morphodynamics and hydrodynamics of river confluences is required to understand these phenomena. In this paper, eddy‐resolving simulations based on laboratory experiments made in a live‐bed model of a mountain‐river confluence are used to provide a detailed description of flow hydrodynamics and implications for morphodynamics. The test case study corresponds to a confluence with an angle of 70°. Numerical simulations are performed for two extreme bathymetric conditions: those at the start of the experiment and when equilibrium morphological conditions are reached. Results of the simulations and experimental observations are used to make inferences on erosion mechanisms during the initial and final states of the erosion/deposition process. The relationship between the coherent structures present in the near‐bed region in the instantaneous and mean flow fields and sediment entrainment/transport is described. The present paper demonstrates the critical role played by large‐scale turbulence generated in the shear layers forming on the side of the tributary flow as it enters the main channel, by the main vortex forming over the discordant bed region surrounding the downstream end of the tributary, as well as by several near‐bed vortices induced by the deflection of the tributary flow by the incoming flow in the main channel. The predicted patterns of bed shear stress are linked to pathways of sediment movement documented in the laboratory experiments, providing a link between the flow and sediment transport. Key Points: Flow hydrodynamics at mountain‐river confluences changes significantly as bed evolves toward equilibrium KH vortices in the shear layer forming at the downstream junction corner plays an important role in transport at mountain‐river confluences Generally, SOV cells do not form at mountain‐river confluences